2021
DOI: 10.1021/acs.jmedchem.1c00881
|View full text |Cite
|
Sign up to set email alerts
|

Potent Neutralizing Antibodies Elicited by RBD-Fc-Based COVID-19 Vaccine Candidate Adjuvanted by the Th2-Skewing iNKT Cell Agonist

Abstract: The development of a safe and effective COVID-19 vaccine is of paramount importance to terminate the current pandemic. An adjuvant is crucial for improving the efficacy of the subunit COVID19 vaccine. α-Galactosylceramide (αGC) is a classical iNKT cell agonist which causes the rapid production of Th1- and Th2-associated cytokines; we, therefore, expect that the Th1- or Th2-skewing analogues of αGC can better enhance the immunogenicity of the receptor-binding domain in the spike protein of SARS-CoV-2 fused with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 79 publications
(198 reference statements)
4
18
0
Order By: Relevance
“…COVID-19 is an acute viral disease caused by SARS-CoV-2 infection, and NKT cells have been reported to play an important role in COVID-19 different stages, including silent SARS-CoV-2 infection stage ( 47 ), progressing stage ( 48 ), convalescence stage ( 15 ), and vaccination ( 16 ). However, little is known about the regulatory mechanisms of NKT cells in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19 is an acute viral disease caused by SARS-CoV-2 infection, and NKT cells have been reported to play an important role in COVID-19 different stages, including silent SARS-CoV-2 infection stage ( 47 ), progressing stage ( 48 ), convalescence stage ( 15 ), and vaccination ( 16 ). However, little is known about the regulatory mechanisms of NKT cells in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that the number of circulating NKT cells in the peripheral blood of patients with COVID-19 decreased (1,(12)(13)(14)(15). NKT cells also showed the ability to enhance vaccinemediated immune response (16), which may be explained by the fact that NKT cells play distinct roles in different stages of COVID-19. To date, the underlying mechanism of NKT cells depletion and the activity regulation during SARS-CoV-2 infection remain to be further elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…The approach has been further revisited by Luo's group in 2013 [62] by implementing the use of galactosyl iodide 8 and d-lyxose 18 for the direct synthesis of disaccharide 19 and providing an improved one-pot deprotection strategy. Another strategy falling under the umbrella of route C has been very recently reported by Wang et al [22] The method exploits olefin cross metathesis between 21 and 22 as the key reaction step. Sharpless epoxidation, followed by epoxide opening with NaN 3 built the αGalCer scaffold 23 in 47 % yield after separation from byproducts.…”
Section: Synthesis Of αGalcermentioning
confidence: 99%
“…While showing promising results, the T H 1/T H 2 cytokine antagonistic effects and the induction of iNKT cell anergy upon repeated administration of αGalCer have been identified as points of concern for its direct application in anti‐tumor therapies. Nonetheless, αGalCer has been also investigated for the treatment of other diseases such as malaria, tuberculosis, lupus, and diabetes mellitus, and in the development of vaccines, where it has been employed as an adjuvant, [16–21] with a recent example in COVID‐19 vaccine candidates [22] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation